THE INFLUENCE OF PRINCIPAL’S TRANSFORMATIONAL LEADERSHIP ON TEACHERS’ WORK MOTIVATION AT SMPN 1 LEUWILIANG - Makarim, Helwiyah; Ana Ratnasari; Ananda Amesa Diwa (Edusifa: Jurnal Pendidikan Islam, 2025)
This study aims to examine the influence of the principal’s transformational leadership on teachers’ work motivation at SMPN 1 Leuwiliang. A quantitative research design was employed with saturated sampling involving all 37 teachers as participants. Data were collected through questionnaires and analyzed using SPSS version 26 (2024). Hypothesis testing using a t-test yielded a t-value of 10.608, which is greater than the critical value of 2.030, with a significance level of 0.000 (<0.05), indicating a significant effect of transformational leadership on teachers’ work motivation. The coefficient of determination (R²) was 0.763, meaning that transformational leadership explains 76.3% of the variance in teacher motivation, while the remaining 23.7% is attributed to other factors not studied here. Keywords: leadership; motivation; principal; teacher; transformational leadership